Analysis and Design of Ultrawideband Circularly Polarized Antenna and Array - Xu, Rui; Gao, Steven Shichang; Liu, Jie; Li, Jian-Ying; Luo, Qi; Hu, Wei; Wen, Lehu; Yang, Xue-Xia; Sri Sumantyo, Josaphat Tetuko (IEEE Transactions on Antennas and Propagation, 2020)
This article presents the design and analysis of an ultrawideband (UWB) circularly polarized (CP) antenna element and its array. First, an UWB CP antenna element using circular-arc-shaped monopole (CASM) with asymmetric ground plane is proposed. Characteristic mode analysis (CMA) is used to investigate its CP operating mechanism, providing physical insights into different modes (mode currents and characteristic radiation fields) at various frequencies. The CMA results show that the asymmetric ground plane makes great contribution to produce CP radiation in the lower frequency band, while another upper CP band is generated by CASM. Thus, the overall 3 dB axial ratio bandwidth (ARBW) of the element can be significantly expanded. Furthermore, a 2 × 2 UWB CP array is designed based on this element. A gradient artificial magnetic conductor (GAMC) with a metal cone is adopted to realize both a low-profile ( 0.1 × λ , where λ is the air-free wavelength at lowest frequency) and the high-gain radiation for the first time. To validate this novel configuration, this array is fabricated and measured. The measured bandwidth ( \vert S_{11} \vert < -10 dB, AR < 3 dB) is approximately 92.3% (1.75-4.75 GHz). It also achieves a wide 3 dB gain bandwidth of 72.3%. Both the simulated and measured results demonstrate that this low-profile high-gain antenna array is promising for applications in wireless systems such as mobile satellite communication system.